Internal Marketing as a Basic in Building Job Satisfaction and Service Quality in Non-Star Hotel in Denpasar - I Gede Rihayana; Putu Pradiva Putra Salain; Putu Agus Eka Rismawan (International Journal of Applied Business and International Management, 2021)
This study aims to analyze the phenomenon of competition in the field of providing hotel lodging services, where the growing development of tourism causes the growth rate of tourism accommodation such as hotels to also increase. This causes non-star hotels as one of the providers of hospitality services to also improve to face this competition by changing the system they have in order to still have an advantage over their competitors. In this study using respondents as many as 91 people with quantitative analysis and testing the research path test was carried out using the Partial Least Square (Smart PLS) 2.0 analysis tool. Based on the results of the research analysis, it was found that internal marketing had a significant positive effect on job satisfaction, job satisfaction had an insignificant positive effect on service quality, and internal marketing had a significant positive effect on service quality. The implementation of this research is to maintain and improve internal marketing by rewarding work performance, to increase job satisfaction by listening more to the suggestions given by employees, and to maintain and improve service quality by always giving personal/special attention to guests who stay and understand the special needs of staying guests. In addition, the results of this study also create a gap for further research, where the relationship between internal marketing and service quality has no significant positive effect.